THE IMPACT OF IDENTITY ON THE STRENGTHENING OF NATIONAL CONSOLIDATION - Do’styorova Sadoqat Norsubxonovna (International Journal of Literature and Language Studies, 2026)
This article analyzes the essence of the phenomenon of identity, its forms of manifestation at the individual and national levels, and the impact of this process on national consolidation - the strengthening of national cohesion - from a socio-philosophical perspective. The author considers identity in its dialectical connection with historical memory, language, value system, and national idea, and also highlights the problems of preserving national identity in the context of globalization.